Studi Literatur : Pengaruh Kinerja Keuangan dan Good Corporate Governance (GCG) terhadap Penghindaran Pajak (Tax Avoidance) - Hesty Retno Hapsari; Aris Eddy Sarwono; Fadjar Harimurti (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study was conducted with the aim of analyzing the influence of financial performance and Good Corporate Governance (GCG) on tax avoidance practices. The method used in this study is a literature study by analyzing and synthesizing 10 published journals related to this topic. Analysis of the study results proves that financial performance such as Return on Assets (ROA) and profitability have a positive relationship with tax avoidance, while Good Corporate Governance (GCG) through an independent board, institutional ownership, and an audit committee can significantly reduce tax avoidance practices. These findings support agency theory which emphasizes the importance of supervision and transparency in controlling conflicts of interest between management and shareholders. This study provides practical implications for regulators and companies to strengthen corporate governance in order to balance tax optimization and tax compliance